Relation of health-related quality of life to near final height and body composition in adolescents with chronic endocrinopathies during transition period - Mittnacht, Janna; Choukair, Daniela; Breil, Thomas; Klose, Daniela; Inta, Ioana; Bettendorf, Markus (Clinical endocrinology, 2020)
Introduction - We evaluated sequelae of disease and therapy in adolescents with chronic endocrinopathies using a medical and psychological workup to record health-related quality of life (HRQoL), near final height (NFH) and body compositions during the transition period from paediatric to adult care.
First published: 18 July 2020
Gesehen am 17.12.2021